2015
DOI: 10.1080/13546805.2015.1042966
|View full text |Cite
|
Sign up to set email alerts
|

Re-examining Kohlberg's conception of morality in schizophrenia

Abstract: These results indicate that performance deficits on moral judgement tasks are not a universal feature of schizophrenia, but rather due to associated difficulties such as those in social cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…1,10 Moreover, people with schizophrenia exhibit many deficits in social cognition, including ToM, 6,7,11,12 which are related to the processes of moral cognition and together form an integral aspect of social functioning. [13][14][15] Research indicates that moral judgment is a complex socio-cognitive process that requires ToM skills. 16 For instance, neurocognitive studies among children show that the observer's knowledge about the mental state of another person (actor) is integrated with their knowledge about the outcome of the actor's behavior.…”
Section: Introductionmentioning
confidence: 99%
“…1,10 Moreover, people with schizophrenia exhibit many deficits in social cognition, including ToM, 6,7,11,12 which are related to the processes of moral cognition and together form an integral aspect of social functioning. [13][14][15] Research indicates that moral judgment is a complex socio-cognitive process that requires ToM skills. 16 For instance, neurocognitive studies among children show that the observer's knowledge about the mental state of another person (actor) is integrated with their knowledge about the outcome of the actor's behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral studies reveal mixed results, showing fragile effects that often depend on question probe and perspective [14,[17][18][19]. Furthermore, common tasks such as Kohlberg's Moral Judgment Interview require verbal abilities ( [20][21][22]) and abstract reasoning, both of which are impaired in SSD [20][21][22]. In general, psychiatric research on moral cognition is not yet conclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the comparability of published studies is limited since not all experiments examine the same dimension of morality, which is assumed to consist of a) the moral decision itself, b) the moral judgment about how appropriate the action is and c) the moral inference describing how a person is perceived based on his/her action and additional information about the person [23]. Studies on SSD revealed evidence for impaired [13,14,17,22] as well as intact moral decision-making [13,[17][18][19]). There is some evidence for impaired moral judgment in SSD [14,24,25], however, a more recent examination merely found prolonged but otherwise intact moral judgments in patients [14].…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent search for an explanation for these early findings on moral reasoning using the MJI, it has been argued that these studies might have underestimated confounding factors like social cognitive deficits and psychopathic personality traits and thus led to a skewed view on moral cognition in schizophrenia (11). This interpretation is supported by evidence suggesting that social cognitive deficits seemed to partially account for patients' poor performance in the MJI (12). In other recent work on moral judgment, rather than moral reasoning, patients with schizophrenia have also been found to employ more utilitarian (or outcome-focused) decisionmaking than healthy controls when asked to judge whether it is morally appropriate for an agent in a moral dilemma scenario to harm one to serve the greater good (13).…”
Section: Introductionmentioning
confidence: 99%